Propagação e controle de Anredera cordifolia (Ten.) Stennis - San Gregorio, João Paulo Ruvieri (Universidade Federal de São Carlos, 2020)
Anredera cordifolia (Ten.) Stennis (Madeira vine) is a succulent vine that produces vegetative structures on its stem, called aerial bulbils that are responsible for the dispersion of this species. This plant has become a possible invader in Brazilian agriculture with records of losses in coffee crops. The objective of this study was to study the influence of dimensional variation and different depths of planting aerial bulbils on the growth and development of A. cordifolia plants, as well as to study the influence of the effect of herbicides on pre and post emergence control of plants. All experiments were carried out in a greenhouse. Experiments for the study of propagation: In experiment 1, a completely randomized design with six replications was used. The treatments consisted of four mass classes (previously established) of aerial bulbils: C1 (0 to ≤ 0.6g), C2 (> 0.6 to ≤ 1.5g), C3 (> 1.5 to ≤ 3.0g) and C4 (> 3.0 to ≤ 12.0g), observing the percentage of viable bulbils (BV), the number of stems per bulbillus (NH/B), the average stem length (CMH), the aerial part dry mass (MSPA) and the emergency speed index (IVE). For experiment 2, a completely randomized design with four replications was used. The emission of plants by bulbilli planted at seven different depths (0, 3, 6, 10, 15, 20 and 30 cm) was verified, NH/B and IVE were observed. Experiments designed to study the management of potted plants: In experiment 1, the control percentage and the MSPA were determined after application in post-emergence in the commercial dose of the herbicides: chlorimuron-ethyl (20 g a.i. ha-1), flumioxazin ( 25 g a.i. ha-1), glyphosate (2.4 g a.i. ha-1), metsulfuron-methyl (6 g a.i. ha-1), saflufenacil (70 g a.i. ha-1) and glyphosate + saflufenacil (1.44 g a.i. ha-1 + 49 g a.i. ha-1) in a completely randomized design in a factorial scheme (herbicides X periods), with four replications. In experiment 2, the number of shoots per bulb (NB/B) was observed after the application of the herbicides: flumioxazin (120 g a.i. ha-1), imazapic (122.5 g a.i. ha-1), indaziflan (92.5 g a.i. ha-1), metribuzin (960 g a.i. ha-1), sulfentrazone (700 g a.i. ha-1) and tebuthiuron (1200 g a.i. ha-1) in pre-emergence of the plants in a completely randomized design, with four replications. Plants from bulbils with greater mass have a fast growth and establishment; the establishment of aerial bulbils on the soil surface has a greater chance of emission of plants with rapid growth; A. cordifolia plants had about 80% control when subjected to the mixture of glyphosate + saflufenacil herbicides.
Propagation and control of Anredera cordifolia (Ten.) Stennis
Keywords: Madeira vine; Binahong; Planta daninha; Propágulo; Brasil; Weed plant; Plant propagule; Brazil; CIENCIAS AGRARIAS::AGRONOMIA::FITOSSANIDADE; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA